Study on the Vectoring Potential of Halyomorpha halys for Pantoea stewartii subsp. stewartii, the Pathogen Causing Stewart’s Disease in Maize - Francesca Costantini; Agostino Strangi; Fabio Mosconi; Leonardo Marianelli; Giuseppino Sabbatini-Peverieri; Pio Federico Roversi; Valeria Scala (Agriculture)
Pantoea stewartii subsp. stewartii (Pss) is a Gram-negative bacterium first documented in North America, and is the causal agent of Stewart’s disease in maize (Zea mays), especially in sweet corn. First identified in North America, it is primarily spread by insect vectors like the corn flea beetle (Chaetocnema Pulicaria) in the United States. However, Pss has since spread globally—reaching parts of Africa, Asia, the Americas, and Europe—mainly through the international seed trade. Although this trade is limited, it has still facilitated the pathogen’s global movement, as evidenced by numerous phytosanitary interceptions. Recent studies in Italy, as indicated in the EFSA journal, reported that potential alternative vectors were identified, including Phyllotreta spp. and the invasive Asian brown marmorated stink bug (Halyomorpha halys); the latter tested positive in PCR screenings, raising concerns due to its broad host range and global distribution. This information has prompted studies to verify the ability of Halyomorpha halys to vector Pss to assess the risk and prevent the further spread of Pss in Europe. In this study, we explored the potential transmission of Pss by the brown marmorated stink bugs in maize plants, following its feeding on Pss-inoculated maize, as well as the presence of Pss within the insect’s body.